Celecoxib inhibits tumor growth and angiogenesis in an orthotopic implantation tumor model of human colon cancer - Wang, L.; Chen, W.; Xie, X.; He, Y.; Bai, X. (Experimental Oncology, 2008)
Aim: To examine the effect of celecoxib on tumor growth and angiogenesis in an orthotopic implantation tumor model of colon cancer. Methods: Human colorectal adenocarcinoma HT-29 cells were implanted subcutaneously in nude mice. Four groups of animals received different doses of celecoxib after tumor implantation. After 42 days, all animals were evaluated for changes in body weight, the volume and weight of colorectal tumors, and tumor growth inhibition. The content of prostaglandin E2 (PGE2) in the tumor tissue homogenate was estimated by radioimmunoassay (RIA). Cyclooxygenase-2 (COX-2) and CD34 expression in tumor tissue was assessed by immunohistochemistry, and the microvessel density (MVD) of tumor tissue was determined. Apoptosis of the tumor cells was detected by the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL). The expression of vascular endothelial growth factor (VEGF) mRNA and matrix metalloproteinase-2 (MMP-2) mRNA extracted from the tumor tissue was analyzed by reverse transcriptase polymerase chain reaction (RT-PCR). Results: There was no statistically significant change in the animals’ body weight between the treatment groups. However, with increasing doses of celecoxib, the volume and weight of the tumor decreased. The rates of tumor growth inhibition for the L (low), M (medium) and H (high) groups were 25.30%, 38.80%, and 76.92%, respectively, which were significant compared to the C (control) group. There were significant differences in COX-2 expression in the tumor tissue between all groups, except between the L and M groups. Celecoxib exposure also reduced PGE2 levels in the tumor tissue homogenates. The level of PGE2 correlated to the weight of tumor (r = 0.8814, P < 0.05) and to COX-2 expression (r = 0.8249, P < 0.05). Compared to the control group, the tumor cells from celecoxib-treated mice had a significantly higher apoptotic index. Celecoxib also decreased CD34+ expression in tumors from treated mice. There were significant differences in the MVD between all groups except between groups H and M. Celecoxib significantly reduced the expression of VEGF and MMP-2 mRNA in the group H but not in L and M groups. The MVD in tumor tissue was closely related to the PGE2 levels, as well as the expression of VEGF and MMP-2 mRNA (r = 0.9006, r = 0.8573 and r = 0.6427, respectively; P < 0.05). Conclusions: By inhibiting COX-2, PGE2 synthesis, and VEGF and MMP-2 mRNA expression in tumor tissue, celecoxib enhances tumor cell apoptosis, thereby inhibiting the growth and angiogenesis of orthotopically implanted tumors in a mouse model of human colorectal cancer. Цель: изучить влияние целекоксиба на рост опухоли и ангиогенез в модели ортопической имплантации опухоли толстой кишки
человека. Методы: клетки колоректальной аденокарциномы человека НT-29 подкожно имплантировали бестимусным мышам.
После имплантации опухоли четыре группы животных получали разные дозы целекоксиба. Через 42 дня изучали изменения
веса животных, объем опухолей, эффект ингибирования роста опухоли. С помощью радиоиммунного анализа (RIA) в гомо- RIA) в гомо ) в гомогенате
опухолей определяли содержание простогландина E2
(PGE2
). В опухолевой ткани иммуногистохимическим методом
выявляли экспрессию циклооксигеназы-2 (COX-2) и CD34 и оценивали плотность микрососудов (MVD). Апоптотические
клетки выявляли методом TUNEL. Экспрессия мРНК фактора роста эндотелия сосудов (VEGF) и металлопротеиназы-2
(MMP-2) в опухолях проанализирована методом обратной транскриптазной реакции (RT-PCR). Результаты: статистически
достоверных различий в весе животных между разными группами обнаружено не было. Вто же время, с увеличением
дозы целекоксиба объем и вес опухоли уменьшался. По сравнению с контрольной группой (C), рост опухоли статистически
достоверно ингибировался в L (низкая доза), M (средняя доза) и H (высокая доза) группах животных на 25,30%, 38,80% и
76,92% соответственно. Были обнаружены значительные отличия в экспрессии COX-2 в опухолевых тканях между всеми
группами животных, кроме групп L и M. Было показано целекоксиб-зависимое уменьшение уровня PGE2
в гомогенатах
опухолей. Уровень PGE2
коррелировал с весом опухоли (r = 0,8814, P < 0,05) и экспрессией COX-2 (r = 0,8249, P < 0,05).
По сравнению с контрольной группой опухолевые клетки мышей, получавших целекоксиб, имели значительно более высокий
апоптотический индекс. Целекоксиб также снижал экспрессию CD34+ на поверхности опухолевых клеток. Были обнаружены
статистически достоверные различия в MVD между всеми исследованными группами, кроме H и M. Целекоксиб способствовал
уменьшению экспрессии мРНК VEGF и MMP-2 в группе Н, но не в группах L и M. MVD в опухолевой ткани кореллировал с
уровнем PGE2
, а также с экспрессией мРНК VEGF и MMP-2 (r = 0,9006, r = 0,8573 и r = 0,6427 соответственно; P < 0,05).
Выводы: целекоксиб способствует апоптозу опухолевых клеток, ингибирует рост опухоли и ангиогенез при ортотопической
имплантации мышам колоректальной аденокарциномы человека. Такой эффект целекоксиба связан с угнетением синтеза
COX-2, PGE2 и экспрессии мРНК VEGF и MMP-2 в опухолевой ткани.